Implementasi Etika dalam Bisnis Islam terhadap Persaingan Usaha Pelaku UMKM di Pasar Senggol Kota Pare-Pare - A. Melantik Rompegading; Lukman; Rais; Shadri (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
This study aims to examine the implementation of ethics in Islamic business towards business competition of MSME actors in Senggol Market, Pare-pare City by focusing on the formulation of the problem about, 1. What is the form of buying and selling activities of MSME actors in Senggol Market, Pare-pare City? 2. What influences the implementation of Islamic business ethics towards MSME actors in Senggol Market, Pare-pare City? This study was conducted using a field research approach through the process of collecting, processing, presenting, and analyzing data in order to reveal the truth of knowledge scientifically, so as to produce valid findings. This method is designed to provide accurate answers to the problems studied. In analyzing the issues discussed, the author utilizes the implementation theory and the theory of Islamic business ethics. The results of this study indicate that the buying and selling activities carried out by MSME actors in Senggol Market, Parepare City can be seen from the aspects of product, price, and service. In addition, there are four main competition factors that occur in this area, namely competition in products, prices, locations, and services. The implementation of Islamic business ethics is measured based on several principles, namely the principles of monotheism, honesty, freedom of will, and responsibility. Most MSME actors have implemented these principles, although there are still some who have not fully implemented them.